(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Abstract. Educational data mining is a growing field of study that aims to improve education by tracking students' progress and attempting to comprehend what they are learning. Receiving students' remarks at the conclusion of the semester, on the other hand, is unsettling and does not benefit students who took the course. For the benefit of current students, feedback should be supplied and managed in real time. This would allow students and teachers to deal with teaching and learning concerns as efficiently as possible. Using feeling analysis methodologies, students' input could show positive or negative ideas as well as more refined feelings regarding their present lectures. Previous research using student response technologies such as clickers, SMS, and mobile phones has shown that feedback may be collected in a variety of methods. The study's goal is to show how social media input may be obtained and how sentiment analytics can aid in the improvement of the educational system. The study, Education Sentiment Analysis, also includes our system.